2021
DOI: 10.7250/bjrbe.2021-16.519
|View full text |Cite
|
Sign up to set email alerts
|

Louvred Noise Barrier for Traffic Noise Reduction

Abstract: Environmental issues near roads become more and more important in our society daily life. One of the most critical environmental issues is traffic noise. The present paper study louvred noise barrier designed by authors. The louvred noise barrier provides sound attenuation while allowing airflow and sunlight through it. Since the airflow resistance of the barrier is low, it requires a shallow foundation compared to conventional noise barriers. The sound attenuation performance of the louvred noise barrier was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
3
0
2
Order By: Relevance
“…Sound attenuation varied between 2 dBA and 17 dBA in equivalent broadband sound level. The barrier setup utilizing mineral wool proved to be most effective in the high-frequency bands [39]. In summary, it can be said that the angle of inclination of the blinds and their thickness have the greatest impact on sound reduction.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Sound attenuation varied between 2 dBA and 17 dBA in equivalent broadband sound level. The barrier setup utilizing mineral wool proved to be most effective in the high-frequency bands [39]. In summary, it can be said that the angle of inclination of the blinds and their thickness have the greatest impact on sound reduction.…”
Section: Discussionmentioning
confidence: 96%
“…Just like in our study, scientists found that an increased reduction in sound pressure level was also noted with the elevation of the louvers' inclination angle. In other studies, a louvered noise barrier for traffic noise reduction was tested [39]. The barrier louvers were covered with mineral wool.…”
Section: Discussionmentioning
confidence: 99%
“…Šie elementai dažniausiai būna pagaminti iš garsą absorbuojančių, minkštų medžiagų arba garsą atspindinčių komponentų. Difraguojančių, skirtingos geometrijos triukšmą mažinančių barjerų elementų efektyvumą tyrė mokslininkai iš viso pasaulio (Asdrubali, 2007;Monazzam & Fard, 2011;Yamamoto, 2015).…”
Section: Triukšmą Mažinančių Barjerų Efektyvumo Priklausomybė Nuo For...unclassified
“…Aplinkos problemos šalia kelių ir geležinkelių tampa vis svarbesnės mūsų visuomenės kasdieniame gyvenime (Astrauskas et al, 2021). Esminis faktorius, darantis didžiausią įtaką aplinkos triukšmo lygiams Kybartų mieste, yra geležinkelio ruožas (Nesterovas-Kybartai-Alvitas), kertantis Kybartų miestą rytų-vakarų kryptimi ir jungiantis Lietuvą su Kaliningrado sritimi vakarinėje miesto dalyje netoli Kybartų magistralės pasienio kontrolės punkto.…”
Section: įVadasunclassified